The Influence of Marital Status on Teacher Income in Bandar Lampung City - Ulul Azmi; Ida Budiarty DA (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research aims to analyze the influence of marital status on teacher income in the city of Bandar Lampung. This type of research is quantitative research. This research uses primary data sourced from surveys and observations. The data used in this research is cross section data from 46 State Elementary Schools (SDN) in 20 sub-districts in Bandar Lampung City. The method used in this research is the multiple linear regression model data analysis method. The research results show that marital status has a significant positive effect on teacher income in Bandar Lampung City.